Desenvolvimento de plataforma de instrumentação virtual para o acionamento, controle e monitoramento de um motor a relutância variável 8/6 - Faria, Victor Henrique da Cunha (2022)
The objective of this work is to develop a virtual instrumentation platform that would allow the drive of an 8/6 SRM, and allow the monitoring of fundamental magnitudes for their study during the experiments, grouping all the functionalities in a single interface. Therefore, this work aimed to contribute to the development of platforms for driving SRM with the aid of techniques from virtual instrumentation, enabling the implementation of future studies on the machine. A robust drive system was used, with capacity to apply the control was embedded in DSP/FPGA of myRIO-1900, communicating with a graphic interface programmed in LabVIEW. The applied data acquisition system was composed by current, voltage, position and torque sensors, providing information for the drive control and for real time inspection of the quantities. To demonstrate the capacity of the platform created, several tests were performed, including the drive with a hysteresis current regulator, speed control and application of an torque estimator. The experimental results showed that the developed platform presented reliable operation, with low measurement errors, and evidenced its flexibility in the insertion of new features.